1999
DOI: 10.1016/s0378-1097(98)00540-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of surface saccharides in two Corynebacterium diphtheriae strains

Abstract: Two Corynebacterium diphtheriae strains were analyzed by assays employing a battery of highly purified fluorescent lectins. From 22 lectins tested only seven with affinity to receptor molecules containing N-acetylglucosamine (D-GlcNAc), Nacetylgalactosamine (D-GalNAc), galactose (D-Gal), mannose-like (D-Man-like) and sialic acid residues showed positive fluorescent labeling. A higher reactivity of Triticum vulgaris (WGA), which binds to sialic acid and/or L-D-GlcNAc-containing residues, and Bandeiraea simplici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…We have observed an absolute reduction in the sialic acid residues and a significant increase in the amounts of D-GlcNAc, D-GalNAc, D-Gal, and D-Man residues in both strains. Sialic acid terminal constituents of cell moieties seemed to raise difficulties in C. diphtheriae adherence to HEp-2 cells, as previously observed with erythrocytes (11).…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…We have observed an absolute reduction in the sialic acid residues and a significant increase in the amounts of D-GlcNAc, D-GalNAc, D-Gal, and D-Man residues in both strains. Sialic acid terminal constituents of cell moieties seemed to raise difficulties in C. diphtheriae adherence to HEp-2 cells, as previously observed with erythrocytes (11).…”
Section: Discussionsupporting
confidence: 64%
“…Sialic acid residues were expressed mainly on the surface of the nonhemagglutinating and highly glassadherent strain 241. It is known that sugar residues, particularly sialic acid residues, contribute to the expression of hydrophilic characteristics and adherence to glass by C. diphtheriae (11). Here we have demonstrated that iron has a regulatory role in the expression of surface carbohydrate moieties of C. diphtheriae strains.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations